Detection of Volatile Constituents from Food Lures by Tephritid Fruit Flies - Tibebe Dejene Biasazin; Haimanot Teklemariam Chernet; Sebastian Larsson Herrera; Marie Bengtsson; Miriam Frida Karlsson; Joelle Kristin Lemmen-Lechelt; Teun Dekker (Insects, 2018)
Tephritid fruit flies require protein for sexual and gonotrophic development. Food-based lures are therefore widely used in strategies to detect and control fruit flies in the Tephritidae family. However, these baits are attractive to a broad range of insect species. We therefore sought to identify volatiles detected by the fly antennae, with the goal to compose lures that more specifically target tephritids. Using gas chromatography-coupled electroantennographic detection (GC-EAD) we screened for antennal responses of four important tephritid species to volatile compounds from five commercially available protein-based baits. Antennal active compounds were reconstituted in synthetic blends for each species and used in behavioral assays. These species-based blends were attractive in olfactometer experiments, as was a blend composed of all antennally active compounds from all the four species we observed (tested only in Bactrocera dorsalis, Hendel). Pilot field tests indicate that the blends need to be further evaluated and optimized under field conditions.